Penentuan Indikator Pengukuran dan Analisis Kinerja Keuangan Perusahaan Konstruksi (Studi Kasus: PT. X (Persero) Tbk) - Fatima, Ima; Medeline, Whenny; Ikhsan, Fitratul (Jurnal Teknik Sipil, 2024)
Abstract Infrastructure development plays a crucial role in economic growth in Indonesia. Despite the high demand for infrastructure, it does not guarantee that construction companies in Indonesia can sustain financially or non-financially because the construction industry is vulnerable to financial risks. This was evident during the Covid-19 pandemic in 2020, where there was a 5.66% decrease in the number of construction companies due to economic slowdown. This correlates with the poor financial performance of construction companies in Indonesia, as seen in one of the state-owned construction companies in Indonesia, which has significant liabilities compared to other state-owned enterprises. Decreases in financial performance can occur in every company if they do not have effective financial management. Therefore, each company needs to implement effective financial performance management by determining appropriate performance measurement indicators and analyzing financial performance to assess the financial health of the company. The research was conducted at PT. X (Persero) Tbk., a state-owned construction company in Indonesia. This research aims to determine the procedure for identifying financial performance indicators, establish these financial performance indicators, and analyze the company's financial performance. The procedure for identifying financial performance indicators was obtained through a literature review and validated through interviews with the company. Subsequently, the financial performance analysis was carried out using financial ratio analysis and the weighting of financial ratio values based on Keputusan Menteri BUMN Nomor Kep-100/MBU/2002, resulting in an assessment of the company's financial health. The analysis results indicate that the financial health of PT. X (Persero) Tbk. fluctuates and is influenced by both internal and external factors.